GA3 application in grapes (Vitis vinifera L.) modulates different sets of genes at cluster emergence, full bloom, and berry stage as revealed by RNA sequence-based transcriptome analysis - Upadhyay, Anuradha; Maske, Smita; Jogaiah, Satisha; Kadoo, Narendra Y.; Gupta, Vidya S. (Functional & Integrative Genomics, 2018)
In grapes (Vitis vinifera L.), exogenous gibberellic acid (GA3) is applied at different stages of bunch development to achieve desirable bunch shape and berry size in seedless grapes used for table purpose. RNA sequence-based transcriptome analysis was used to understand the mechanism of GA3 action at cluster emergence, full bloom, and berry stage in table grape variety Thompson Seedless. At cluster emergence, rachis samples were collected at 6 and 24 h after application of GA3, whereas flower clusters and berry samples were collected at 6, 24, and 48 h after application at full bloom and 3–4 mm berry stages. Seven hundred thirty-three genes were differentially expressed in GA3-treated samples. At rachis and flower cluster stage respectively, 126 and 264 genes were found to be significantly differentially expressed within 6 h of GA3 application. The number of DEG reduced considerably at 24 h. However, at berry stage, major changes occurred even at 24 h and a number of DEGs at 6 and 24 h were 174 and 191, respectively. As compared to upregulated genes, larger numbers of genes were downregulated. Stage-specific response to the GA3 application was observed as evident from the unique set of DEGs at each stage and only a few common genes among three stages. Among the DEGs, 67 were transcription factors. Functional categorization and enrichment analysis revealed that several transcripts involved in sucrose and hexose metabolism, hormone and secondary metabolism, and abiotic and biotic stimuli were enriched in response to application of GA3. A high correlation was recorded for real-time PCR and transcriptome data for selected DEGs, thus indicating the robustness of transcriptome data obtained in this study for understanding the GA3 response at different stages of berry development in grape. Chromosomal localization of DEGs and identification of polymorphic microsatellite markers in selected genes have potential for their use in breeding for varieties with improved bunch architecture.
Keywords: Bunch architecture; GA3 response; Microsatellite markers; RNA seq; Transcription factors; Vitis vinifera